DOGS' UNDERSTANDING OF HUMAN WORDS: A PSYCHOLINGUISTIC APPROACH - Aisya Risni Lamanci; Nagita Syahwania Djenaan; Susan Karim; Amelia Idris; Moh. Zukhrian Darsa; Muziatun Muziatun (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study explores dogs’ understanding of human words from a psycholinguistic perspective. The study aims to examine how dogs respond to lexical cues, prosodic features, and human body language during communication. A qualitative approach was employed using Netnographic Audiovisual Analysis of selected YouTube videos featuring human–dog interactions. The collected data were analyzed to identify patterns of canine responses to verbal commands and communicative signals. The findings suggest that dogs may associate specific words with actions and respond not only to lexical information but also to intonation and contextual cues. Furthermore, dogs demonstrate behaviors that reflect associative learning and attention to human communication. These findings contribute to the understanding of cross-species communication and provide insights into psycholinguistic processes involved in canine language comprehension.